Regulation, Competition, and Liberalization - Armstrong, Mark; Sappington, David E. M (Journal of Economic Literature, 2006)
In many countries throughout the world, regulators are struggling to determine whether and how to introduce competition into regulated industries. This essay examines the complexities involved in the liberalization process. While stressing the importance of case-specific analyses, this essay distinguishes liberalization policies that generally are procompetitive from corresponding anticompetitive liberalization policies.